Preparation method of flexible automatic temperature limiting conductive material

By using EVA, PA and SA in PTC materials, adjusting their proportions, and combining them with interfinger electrodes, the problem of insufficient thermal sensitivity and thermal stability of existing PTC materials is solved, and the Curie temperature is achieved in the range of 40-60℃, improving the thermal sensitivity and PTC strength of the device.

CN119591968AActive Publication Date: 2025-03-11JIANGNAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411727315.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11
Estimated Expiration
2044-11-28

Smart Images

  • Figure CN119591968A_ABST
    Figure CN119591968A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a flexible automatic temperature limiting conductive material, and belongs to the technical field of functional material preparation. The normal-temperature flexible thermal management material is prepared by using EVA as a supporting material, hexadecanoic acid and stearic acid as phase-change materials and graphite as a conductive filler and adjusting the use ratio of the materials, so that excellent temperature control performance and a relatively low conversion temperature point are achieved. Meanwhile, the material is combined with the interdigital electrode, so that the heat sensitivity of the device is improved, the resistance value of the composite material is reduced, and the use requirements under different powers are met by adjusting the pattern of the interdigital electrode, so that the response speed of the whole composite material to the temperature is improved; high PTC strength and good room temperature resistivity are achieved by changing the content of the conductive filler in the composite material. Under different proportions of components, the composite material has good electric heating performance, and meanwhile, under the conditions of different voltages, cyclic pressurization and further pressurization, the temperature control condition is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a flexible automatic temperature-limiting conductive material, and belongs to the technical field of functional material preparation. Background Art

[0002] With the popularity of wearable devices, how to achieve effective thermal management in a limited space has become a design challenge to ensure the comfort and performance of the device. In existing thermal control systems, fixed-value resistors are usually used as heating elements, and the heating power of the resistors needs to be controlled by adjusting the input power of the heating circuit. However, since the resistivity of the common resistor is almost constant, this requires the thermal control system to monitor temperature and current. If the common resistors in the system are replaced with materials that can adjust their resistivity as the temperature changes, the system can be greatly simplified.

[0003] Positive temperature coefficient (PTC) composite materials can show resistance changes as the temperature rises. Polymer PTC materials are mainly composed of polymer matrix and conductive filler, and the matrix material is usually mainly crystalline and semi-crystalline matrix (PP, HDPE, EVA, etc.). For polymer PTC composite materials, when the temperature reaches its transition temperature, the crystalline polymer changes in volume due to phase change, increasing the average distance between the conductive particles, thereby destroying the structure of the conductive network. In the polymer matrix, the distribution of conductive fillers will change with the change of temperature, which will eventually lead to a significant increase in the resistivity of the PTC material, thereby achieving the effect of disconnecting the conductive network. The higher the strength of the PTC, the more thorough the destruction of the conductive network.

[0004] As a key parameter of PTC materials, Curie temperature reveals the threshold temperature when the maximum resistance of PTC materials changes sharply. Nowadays, the Curie temperatures of most polymer-based PTC material systems are mainly concentrated in the range of 90-160°C, but such a high Curie temperature cannot meet the requirements of thermal control devices at room temperature such as household electronic devices, capacity batteries, and wearable electronics. For most electronic components, controlling the ambient temperature within the range of 40-60°C can ensure the normal operation of the device.

[0005] Although the phase change temperature transition points of hexadecanoic acid (PA) and stearic acid (SA) are within this range, the thermal conductivity of hexadecanoic acid (PA) and stearic acid (SA) is low, which limits their use in applications that require rapid thermal response. Organic acid phase change materials have poor stability at the phase change temperature transition point, and volume changes may occur during the phase change process, leading to leakage and reduced thermal conductivity area, causing increased thermal resistance.

[0006] Most existing PTC materials have the problems of too high or too low Curie temperature, low thermal sensitivity, low overall flexibility of the composite material, low PTC strength, and low overall thermal stability. Summary of the invention

[0007] In order to obtain a material with a Curie temperature in the range of 40-60°C, meet the requirements of thermal control devices at room temperature for household electronic devices, capacity batteries, wearable electronics, etc., and ensure the normal operation of the device, the present invention uses EVA as a supporting material, hexadecanoic acid (PA) and stearic acid (SA) as phase change materials, and prepares a flexible thermal management material that can be used for household electronic appliances. By adjusting the ratio of PA and SA, excellent temperature control performance and a suitable Curie temperature point are achieved; at the same time, the PTC composite material is combined with the interdigital electrode, which greatly improves the thermal sensitivity of the device, reduces the resistance of the composite material, and improves the overall response speed of the PTC composite material to temperature; by changing the content of the conductive filler (GP) in the composite material to achieve a higher PTC strength and a resistance value of less than 1000Ω at room temperature. Under the proportion components of the present invention, the PTC composite material has good electrothermal performance, and the temperature control is good under different voltages, cyclic pressurization and further pressurization; and during the pressurization process, the temperature is stable and the volatility is small.

[0008] The present invention provides a PTC composite material, the composite material comprising: an ethylene-vinyl acetate copolymer matrix material, a phase change material, and a conductive filler, wherein the phase change material is one or more of stearic acid, lauric acid, hexadecanoic acid, pentadecanoic acid, and eicosanoic acid, and the conductive filler comprises one or more of carbon black, carbon nanotubes, graphite powder, and graphene;

[0009] In the composite material, the mass fraction of ethylene-vinyl acetate copolymer is 4-30%, preferably 10-20%, and more preferably 20%; the mass fraction of conductive filler is 4-16%, preferably 6-10%; the mass fraction of phase change material is 4-30%, preferably 10-20%, and more preferably 20%. The mass ratio of phase change material and ethylene-vinyl acetate copolymer is 0.5-1.5:1, and the rest is organic solvent. The organic solvent includes but is not limited to toluene, tetrahydrofuran, and N,N-dimethylformamide.

[0010] In one embodiment of the present invention, the phase change material is hexadecanoic acid and stearic acid; the ratio of hexadecanoic acid to stearic acid added is 1-4:1-4.

[0011] In one embodiment of the present invention, the ethylene-vinyl acetate copolymer matrix material is EVA with a mass fraction of VA of 10 to 30%.

[0012] In one embodiment of the present invention, the organic solvent includes but is not limited to toluene, tetrahydrofuran, and N,N-dimethylformamide.

[0013] The present invention also provides a method for preparing a PTC material, comprising the following steps:

[0014] (1) adding ethylene vinyl acetate to an organic solvent, shaking at 1000-2000 rpm for 1-5 min, stirring at 600-800 rpm for 6-10 h at 25-40° C. after homogenization, to obtain an EVA solution with a mass fraction of 4-30%, preferably 10-20%, and more preferably 20%;

[0015] (2) adding a phase change material to the EVA solution obtained in step (1), oscillating at 1000-2000 rpm for 1-5 min, stirring at 600-800 rpm for 6-10 h at 25-40° C. after homogenization, to obtain an EVA-phase change material mixed solution, wherein the amount of the phase change material added is 4-30%, preferably 10-20%, and more preferably 20%; the phase change material is one or more of stearic acid, lauric acid, hexadecanoic acid, pentadecanoic acid, and eicosanoic acid; the mass ratio of the amount of the phase change material added to the amount of ethylene-vinyl acetate copolymer added is 0.5-1.5:1;

[0016] (3) Adding a conductive filler to the EVA-phase change material mixed solution obtained in step (2), wherein the mass fraction of the conductive filler in the mixed solution is 4-16%, preferably 6-10%, shaking at 1000-2000 rpm for 1-5 min, stirring at 25-40° C. and 600-800 rpm for 6-10 h, and vacuum dispersing to obtain a PTC composite material; the conductive filler includes but is not limited to one or more of carbon black, carbon nanotubes, graphite powder and graphene.

[0017] In one embodiment of the present invention, the ethylene-vinyl acetate copolymer matrix material is EVA, and the mass fraction of VA in the EVA is 10-30%.

[0018] In one embodiment of the present invention, the conductive filler is spherical graphite GP; preferably, the spherical graphite GP is first dried in an oven at 50-90° C. for 20-30 hours, and then ball-milled in a ball mill at a speed of 200-500 rpm for 4-8 hours to make the grinding and dispersion more uniform.

[0019] In one embodiment of the present invention, after adding the conductive filler to the EVA-phase change material mixed solution, the mixture is shaken, ultrasonically treated for 1 to 10 minutes, and stirred at 400 to 800 rpm for 4 to 8 hours at 25 to 40°C.

[0020] In one embodiment of the present invention, the vacuum dispersion is performed by mixing and dispersing the mixture in a vacuum at 1500 to 3000 rpm for 5 to 15 minutes using a vacuum demoulding and degassing machine.

[0021] In one embodiment of the present invention, the phase change material is hexadecanoic acid and stearic acid; the ratio of hexadecanoic acid to stearic acid added is 1-4:1-4.

[0022] In one embodiment of the present invention, the ethylene-vinyl acetate copolymer matrix material is EVA260 and / or EVA180.

[0023] In one embodiment of the present invention, the organic solvent includes but is not limited to toluene, tetrahydrofuran, and N,N-dimethylformamide.

[0024] The present invention provides a method for improving the response speed of a PTC composite material to temperature and / or the PTC strength. The method comprises the following steps: using ethylene-vinyl acetate copolymer as a matrix material, hexadecanoic acid and stearic acid as phase change materials, and one or more of carbon black, carbon nanotubes, graphite powder and graphene as conductive fillers to prepare the PTC composite material;

[0025] The hexadecanoic acid and stearic acid are added in a ratio of 1-4:1-4.

[0026] In one embodiment of the present invention, the ethylene-vinyl acetate copolymer matrix material is EVA, and the mass fraction of VA in the EVA is 10-30%.

[0027] In one embodiment of the present invention, the method specifically comprises:

[0028] (1) adding ethylene vinyl acetate to an organic solvent, shaking at 1000-2000 rpm for 1-5 min, stirring at 600-800 rpm for 6-10 h at 25-40° C. after homogenization, to obtain an EVA solution with a mass fraction of 4-30%, preferably 10-20%, and more preferably 20%;

[0029] (2) adding a phase change material to the EVA solution obtained in step (1), oscillating at 1000-2000 rpm for 1-5 min, stirring at 600-800 rpm for 6-10 h at 25-40° C. after homogenization, to obtain an EVA-phase change material mixed solution, wherein the amount of the phase change material added is 4-30%, preferably 10-20%, and more preferably 20%; the phase change material is one or more of stearic acid, lauric acid, hexadecanoic acid, pentadecanoic acid, and eicosanoic acid; the mass ratio of the amount of the phase change material added to the amount of ethylene-vinyl acetate copolymer added is 0.5-1.5:1;

[0030] (3) Adding a conductive filler to the EVA-phase change material mixed solution obtained in step (2), wherein the mass fraction of the conductive filler in the mixed solution is 4-16%, preferably 6-10%, shaking at 1000-2000 rpm for 1-5 min, stirring at 25-40° C. and 600-800 rpm for 6-10 h, and vacuum dispersing to obtain a PTC composite material; the conductive filler includes but is not limited to one or more of carbon black, carbon nanotubes, graphite powder and graphene.

[0031] In one embodiment of the present invention, the ethylene-vinyl acetate copolymer matrix material is EVA260 and / or EVA180.

[0032] In one embodiment of the present invention, the organic solvent includes but is not limited to toluene, tetrahydrofuran, and N,N-dimethylformamide.

[0033] The present invention also provides a flexible automatic temperature-limiting electric heater, which is composed of the PTC composite material prepared by the above method, an electrode, and a flexible substrate.

[0034] In one embodiment of the present invention, the PTC composite material is compounded with the electrode to form a film by using an additive manufacturing process.

[0035] In one embodiment of the present invention, the additive manufacturing process includes but is not limited to one or more of screen printing, coating, and spin coating.

[0036] In one embodiment of the present invention, the additive manufacturing process further includes inkjet printing, screen printing, and gravure / letterpress printing.

[0037] In one embodiment of the present invention, the thickness of the flexible automatic temperature-limiting electric heater is 30-200 μm.

[0038] In one embodiment of the present invention, after the PTC composite material is compounded with the electrode, the sheet resistance of the PTC composite material after drying is 100-1000Ω.

[0039] The present invention also provides the above-mentioned PTC composite material or the above-mentioned preparation method or the use of the above-mentioned method in the preparation of lithium batteries, self-regulating heating components, temperature sensors, detectors, and instruments requiring temperature control.

[0040] The present invention also provides the above PTC composite material or the above preparation method or the application of the above method in preparing electrodes.

[0041] Beneficial Effects

[0042] (1) The present invention adjusts the temperature control point range to (40°C-52°C) by adjusting the proportion of phase change energy storage materials. The response time of the material system to temperature is about 5s, and its overall temperature control accuracy is ±0.4°C. The overall PTC strength is improved by 4.5 orders of magnitude, and it is basically stable after three hot and cold cycles.

[0043] (2) The PTC material prepared by the present invention has a low percolation threshold, uniform analysis of the conductive material, good flexibility, light weight, and resistance to bending; it has high voltage breakdown resistance, and can be restored to its initial state after pressure is applied, and still has the ability to disconnect the circuit;

[0044] (3) The combination of the PTC material prepared by the present invention and the silver electrode can greatly improve the thermal sensitivity of the device and reduce the resistance of the composite material. At the same time, by adjusting the interdigital spacing of the silver electrode, different patterns can be obtained to meet different power requirements;

[0045] (4) The patterning process (such as inkjet printing, screen printing, aerosol printing, etc.) used in the present invention can make the overall heating of electronic components more uniform, the heat distribution more concentrated, and reduce the phenomenon of hot spots on the surface; the process of the present invention is simple, the temperature control point is in line with the normal temperature range of electronic components, and the experiment has high reproducibility, low energy consumption, safety, and the use of cheap and environmentally friendly materials without pollutants, which can realize the mass production of PTC ink. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of the preparation of EVA / PA / SA / GP.

[0047] Figure 2 Schematic diagram of the process of EVA / PA / SA / interdigitated electrode pattern, where (a) is a schematic diagram of the interdigitated electrode; (b) is the film layer structure of the electric heating film; and (c) is a schematic diagram of the electric heating film.

[0048] Figure 3 Electrothermal performance diagram of cyclic step-up of composite materials at different ratios.

[0049] Figure 4 Temperature response diagram of composite materials with different GP contents under different voltages. DETAILED DESCRIPTION

[0050] Ethylene vinyl acetate (EVA260) used in the following examples was purchased from DuPont Company, USA.

[0051] Example 1: Preparation of EVA / PA / SA / GP composite material

[0052] The specific preparation process is as follows (the preparation diagram of EVA / PA / SA / GP composite material is as follows Figure 1 shown):

[0053] (1) placing 50 nm spherical graphite GP in an oven and drying it at 80 °C for 24 h, then placing the spherical GP in a ball mill and ball milling it at a speed of 400 rpm for 6 h to obtain a spherical graphite GP powder with more uniform grinding and dispersion;

[0054] (2) Preparation of EVA / PA / SA / GP composite materials:

[0055] After adding ethylene vinyl acetate (EVA) to toluene, the mixture was shaken at 1500 rpm for 1 min, homogenized with a homogenizer (2000 rpm, 10 min), and then magnetically stirred at 400 rpm for 6 h at 40° C. to obtain a 20% EVA toluene solution;

[0056] Hexadecanoic acid (PA) and stearic acid (SA) were sequentially added to the EVA toluene solution, and then oscillated at 1500 rpm for 1 min using an oscillator, homogenized with a homogenizer (2000 rpm, 10 min), and then magnetically stirred at 400 rpm for 6 h at 25° C. to obtain an EVA-PA-SA mixed toluene solution;

[0057] Among them, the addition amounts of ethylene vinyl acetate (EVA), hexadecanoic acid (PA) and stearic acid (SA) are shown in Table 1:

[0058] Table 1: Concentration of each substance in the composite material

[0059]

[0060]

[0061] (3) 0.24 g of the spherical graphite GP powder obtained in step (1) was added to the EVA-PA-SA mixed toluene solution to make the mass fraction of the spherical graphite GP be 7%, and the mixture was oscillated at 1500 rpm for 1 min, and ultrasonically treated at 40 kHz for 5 min, and then stirred at 25 ° C. and 600 rpm for 6 h. After stirring, a vacuum demolding and degassing machine was used to mix and disperse at 2000 rpm for 10 min to obtain EVA / PA / SA (5:4:1) / GP-7% composite material, EVA / PA / SA (5:1:4) / GP-7% composite material, EVA / PA / SA (5:2:3) / GP-7% composite material, EVA / PA / SA (5:3:2) / GP-7% composite material, EVA / PA (1:1) / GP-7% composite material, and EVA / SA (1:1) / GP-7% composite material, respectively.

[0062] Example 2: Preparation of EVA / PA / SA / GP composite material

[0063] The specific implementation method is the same as Example 1, except that the mass fraction of GP is 0%, 6%, 8%, 9%, and 10%, the mass fraction ratio of EVA / PA / SA is 5:4:1, and other conditions remain unchanged. The specific steps are as follows:

[0064] (1) placing 50 nm spherical graphite GP in an oven and drying it at 80 °C for 24 h, then placing the spherical GP in a ball mill and ball milling it at a speed of 400 rpm for 6 h to obtain a spherical graphite GP powder with more uniform grinding and dispersion;

[0065] (2) Preparation of EVA / PA / SA / GP composite materials:

[0066] After adding ethylene vinyl acetate (EVA) to toluene, the mixture was shaken at 1500 rpm for 1 min, homogenized with a homogenizer (2000 rpm, 10 min), and then magnetically stirred at 400 rpm for 6 h at 40° C. to obtain a 20% EVA toluene solution;

[0067] After adding hexadecanoic acid (PA) and stearic acid (SA) to the above EVA toluene solution in sequence, the mixture was oscillated at 1500 rpm for 1 min, homogenized with a homogenizer (2000 rpm, 10 min), and then magnetically stirred at 400 rpm for 6 h at 25° C. to obtain an EVA-PA-SA mixed toluene solution (wherein the final mass fraction of hexadecanoic acid (PA) in the solution was 16%, and the final mass fraction of stearic acid (SA) in the solution was 4%);

[0068] The spherical graphite GP powder obtained in step (1) was added to the EVA-PA-SA mixed toluene solution, so that the mass fraction of the spherical graphite GP was 0%, 6%, 8%, 9%, and 10%, respectively. After 1500 rpm oscillation for 1 min, ultrasonic treatment was performed at 40 kHz for 5 min, and then stirred at 25 ° C and 600 rpm for 6 h. After the stirring was completed, a vacuum demolding and degassing machine was used to mix and disperse at 2000 rpm for 10 min to obtain the following:

[0069] EVA / PA / SA (5:4:1) composite material, EVA / PA / SA (5:4:1) / GP-6% composite material, EVA / PA / SA (5:4:1) / GP-8% composite material, EVA / PA / SA (5:4:1) / GP-9% composite material, EVA / PA / SA (5:4:1) / GP-10% composite material.

[0070] Example 3: Performance test of composite materials in EVA / PA / SA-GP electric heating film

[0071] 1. Preparation of electric heating film

[0072] The composite materials in Examples 1 to 2 were prepared into EVA / PA / SA-GP electric heating films, and the electric heating films were used to further measure the various properties of the composite materials. The preparation method is as follows (the process schematic diagram of the EVA / PA / SA / interdigital electrode pattern is shown in FIG. Figure 2 shown):

[0073] A silver paste interdigital electrode pattern was printed by screen printing, and the silver paste interdigital electrode was covered on polyethylene terephthalate (PET) as a flexible substrate. The prepared EVA / PA / SA / GP composite material was evenly coated on the surface of the silver paste interdigital electrode. The size was fixed to 25×30 mm and the thickness was controlled to 120 μm to obtain an electric heating film. The obtained electric heating film was vacuum dried at 45°C for 24 hours to finally obtain the EVA / PA / SA / GP electric heating film.

[0074] 2. Detection of PTC performance in electric heating film

[0075] (1) PTC performance of composite materials in electric heating films

[0076] The PTC properties of the composite material EVA / PA / SA in the electric heating film at different PA / SA ratios are shown in Table 2.

[0077] Table 2: Properties of composite materials in electric heating films

[0078]

[0079] It can be seen that the resistance of the composite materials in the electric heating film at different PA / SA ratios increases geometrically with the increase of temperature, showing obvious PTC behavior. The Curie temperature of the composite materials is roughly concentrated at 48°C, which is related to the structural transformation of the phase change material in the molten state and the conduction of temperature in the composite materials.

[0080] The PTC strength of the composite material in the electric heating film is shown in Table 3:

[0081] Table 3: PTC strength of composite materials in electric heating films

[0082] Composite materials in electric heating films PTC Strength EVA / PA / SA(5:4:1) / GP-7% 3.66 EVA / PA / SA(5:1:4) / GP-7% 3.84 EVA / PA / SA(5:2:3) / GP-7% 2.78 EVA / PA / SA(5:3:2) / GP-7% 3.47 EVA / PA(1:1) / GP-7% 4.4 EVA / SA(1:1) / GP-7% 3.98 EVA / PA / SA(5:4:1) / GP-8% 4.31 EVA / PA / SA(5:4:1) / GP-9% 3.47 EVA / PA / SA(5:4:1) / GP-10% 2.86

[0083] The difference in PTC strength of composite materials at different ratios is related to their different conductive network structures and the distribution of conductive fillers in the composite materials.

[0084] When the GP mass fraction is 8%, the composite material in the electric heating film responds to temperature faster as a whole, indicating that the conductivity content is near the critical percolation threshold and the resistance change rate is high, thus showing good temperature sensitivity; when the conductive filler content exceeds 8%, too many contact points appear in its conductive network, resulting in the inability to further destroy the conductive network structure, thereby affecting the PTC performance of the composite material in the electric heating film.

[0085] (2) Electrothermal properties of composite materials in composite membranes

[0086] The temperature response, maximum temperature and electric heating cycle stability of the electric heating film were tested, and the results are as follows:

[0087] (a) Thermal response under different voltages

[0088] Depend on Figure 3 It can be seen that:

[0089] The composite materials EVA / PA (1:1) / GP-7% and EVA:PA:SA (5:4:1) / GP-7% in the electric heating film gradually increase in temperature under the step cycle voltage of 24V-72V, and basically no temperature overshoot occurs. Under the step cycle voltage of 72V-120V, its stable temperature no longer increases further with the increase of voltage. Similar change patterns are also shown under other ratios.

[0090] It can be seen that the composite materials in the electric heating films with different PA / SA ratios have different thermal effects under different voltages. As the voltage gradually increases, their temperature remains basically stable. After power is turned on, the composite materials quickly convert electrical energy into thermal energy, resulting in an increase in the surface temperature of the composite materials, which conforms to Joule's law.

[0091] The obtained EVA / PA / SA-GP electric heating film was subjected to 48V, and a thermal imager was used to capture the surface temperature and distribution of the composite material in real time. The maximum surface temperature of the composite material in the electric heating film at different PA / SA ratios is shown in Table 4:

[0092] Table 4: Maximum surface temperature of composite materials in electric heating film

[0093] Composite materials in electric heating films Maximum surface temperature (℃) EVA / PA / SA(5:4:1) / GP-7% 48.3 EVA / PA / SA(5:1:4) / GP-7% 46.1 EVA / PA / SA(5:2:3) / GP-7% 40.9 EVA / PA / SA(5:3:2) / GP-7% 44.7 EVA / PA(1:1) / GP-7% 44.7 EVA / SA(1:1) / GP-7% 42.1

[0094] The composite material EVA / PA / SA (5:4:1) in the electric heating film has basically no conductivity, so its electrothermal performance is not studied.

[0095] The temperature response results of the composite materials in the electric heating film with different GP contents under different voltages are shown in Figure 2. Figure 4 As shown in Table 5:

[0096] Table 5: Temperature response results at different voltages

[0097]

[0098] The temperature response results of the electric heating films with different GP contents under different voltages are as follows: Figure 4 As shown in (ab), the composite materials in the electric heating films prepared with different mass fractions of GP have a faster overall response speed to temperature, and the composite materials have high temperature sensitivity. The temperature can be stabilized within a controllable range within 20 seconds immediately after pressurization.

[0099] (b) Temperature control under cyclic voltage

[0100] Figure 4 In cd, the temperature control of the composite material in the electric heating film prepared by GP with different mass fractions under cyclic voltage is shown, and the stability of the electric heating film is reflected by the change of its resistance during cooling. The smaller the change of resistance, the higher the stability of its cyclic heating and cooling. Specifically:

[0101] The temperature of the composite material EVA / PA / SA (5:4:1) / GP-7% in the electric heating film remains basically unchanged under cyclic pressure, but the resistance value changes greatly. During the initial pressure application, the temperature overshoot phenomenon is obvious.

[0102] The composite material EVA / PA / SA (5:4:1) / GP-9% composite material in the electric heating film has good stability and good overall temperature control performance under cyclic pressure.

[0103] It can be seen that the stable temperature of the composite materials in the electric heating films prepared with different mass fractions of GP under cyclic voltage is basically the same, indicating that the electric heating film has good stability and cooling repeatability.

[0104] Example 4: Effect of the proportion of phase change material and ethylene-vinyl acetate copolymer on composite materials

[0105] The specific implementation is the same as in Example 1, except that the ratio of the phase change material to the ethylene-vinyl acetate copolymer is adjusted to: 3:7, 4:6, 7:3; that is, adjusted to:

[0106] (1) The mass fraction of EVA in the solvent is 12%, the final mass fraction of hexadecanoic acid (PA) in the solution is 14%, and the final mass fraction of stearic acid (SA) in the solution is 14%;

[0107] (2) The mass fraction of EVA in the solvent is 16%, the final mass fraction of hexadecanoic acid (PA) in the solution is 12%, and the final mass fraction of stearic acid (SA) in the solution is 12%;

[0108] (3) The mass fraction of EVA in the solvent is 28%, the final mass fraction of hexadecanoic acid (PA) in the solution is 6%, and the final mass fraction of stearic acid (SA) in the solution is 6%;

[0109] EVA:PA:SA (3:3.5:3.5) composite materials, EVA:PA:SA (4:3:3) composite materials and EVA:PA:SA (7:1.5:1.5) composite materials were prepared respectively.

[0110] The results show:

[0111] The encapsulation performance of EVA:PA:SA (3:3.5:3.5) composite materials and EVA:PA:SA (4:3:3) composite materials is poor, and there is a slight precipitation of phase change material on their surface. The PTC performance of EVA:PA:SA (7:1.5:1.5) composite materials is poor, and the overall temperature control accuracy is not high.

[0112] Comparative Example 1: Effects of different support materials on composite materials

[0113] The specific implementation method is the same as Example 1 (the mass fraction ratio of EVA / PA / SA is 5:4:1), except that the supporting material ethylene-vinyl acetate EVA is replaced with high-density polyethylene HDPE, polylactic acid PLA, and polyvinyl alcohol PVA to prepare a composite material.

[0114] The results show that when plastic particles such as high-density polyethylene (HDPE) or polylactic acid (PLA) are used, due to their high melting point, existing solvents are difficult to fully dissolve them, and the solution mixing method of the present invention cannot be used to prepare them into PTC materials.

[0115] When polyvinyl alcohol (PVA) is used as the supporting material, it exhibits excellent flexibility as a whole, but its PTC performance is poor, and the degree of change in resistance is only about 1 order of magnitude, so it does not have excellent PTC performance.

[0116] Comparative Example 2: Effects of different phase change materials on composite materials

[0117] The specific implementation method is the same as Example 1, except that the phase change material PA / SA is replaced with dodecanoic acid, tetradecanoic acid, paraffin wax, and wax emulsion to prepare the composite material; the specific steps are as follows:

[0118] (1) placing 50 nm spherical graphite GP in an oven and drying it at 80 °C for 24 h, then placing the spherical GP in a ball mill and ball milling it at a speed of 400 rpm for 6 h to obtain a spherical graphite GP powder with more uniform grinding and dispersion;

[0119] (2) Preparation of EVA / phase change material / GP composite materials:

[0120] After adding ethylene vinyl acetate (EVA) to toluene, the mixture was shaken at 1500 rpm for 1 min using an oscillator, homogenized with a homogenizer for 10 min, and then magnetically stirred at 400 rpm for 6 h at 40° C. to obtain an EVA toluene solution with a mass fraction of 20%;

[0121] After the phase change material was added to the above EVA toluene solution in sequence, the mixture was oscillated at 1500 rpm for 1 min, homogenized with a homogenizer for 10 min, and then magnetically stirred at 400 rpm for 6 h at 25° C. to obtain an EVA-phase change material mixed toluene solution (wherein the final mass fraction of the phase change material in the solution was 20%).

[0122] 0.24 g of the spherical graphite GP powder obtained in step (1) was added to the EVA-phase change material mixed toluene solution to make the mass fraction of the spherical graphite GP 7%. The mixture was oscillated at 1500 rpm for 1 min and ultrasonically treated at 40 kHz for 5 min. The mixture was stirred at 25° C. and 600 rpm for 6 h. After the stirring was completed, a vacuum demolding and degassing machine was used to mix and disperse the mixture at 2000 rpm for 10 min to obtain an EVA / phase change material / GP-7% composite material.

[0123] The results show that it is difficult to fully dissolve the wax emulsion part through the solution method, and the overall preparation process is complicated; while in the form of dodecanoic acid and tetradecanoic acid, the overall Curie temperature point is low, and the resistivity of the composite material at room temperature is high, the PTC performance is poor, and the thermal repeatability is lower than that of PA / SA, which cannot meet the set requirements.

[0124] Comparative Example 3: Effects of different conductive fillers on composite materials

[0125] Specific implementation method The composite material is prepared in the same manner as in Example 1 (the mass fraction ratio of EVA / PA / SA is 5:4:1), except that the conductive filler GP is replaced by carbon nanotubes, carbon black and expandable graphite.

[0126] The results show that when expandable graphite is used as a conductive filler, due to its specific worm structure, it will produce certain agglomeration and is difficult to disperse evenly, and there is basically no PTC phenomenon as a whole; when carbon nanotubes are used as conductive fillers, due to the high degree of entanglement between the tubes, the agglomeration phenomenon is more obvious, and there is basically no PTC phenomenon as a whole; when carbon black is used as a conductive filler, due to the large specific surface area between the materials, there is still a certain agglomeration, and the PTC phenomenon is weak.

[0127] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A PTC composite material, characterized in that: The PTC composite material includes: an ethylene-vinyl acetate copolymer matrix material, a phase change material, and a conductive filler. The phase change material is hexadecanoic acid and stearic acid. The mass ratio of hexadecanoic acid and stearic acid added is 1-4:1-4. The conductive filler includes but is not limited to graphite powder and graphene.

2. The PTC composite material according to claim 1, characterized in that: In the PTC composite material, the mass fraction of ethylene-vinyl acetate copolymer is 4-30%; the mass fraction of conductive filler is 4-16%; the mass ratio of phase change material and ethylene-vinyl acetate copolymer is 0.5-1.5:1, and the rest is organic solvent.

3. The PTC composite material according to claim 1 or 2, characterized in that: The organic solvent includes but is not limited to toluene, tetrahydrofuran, and N,N-dimethylformamide; preferably, the ethylene-vinyl acetate copolymer matrix material is EVA, and the mass fraction of VA in the EVA is 10-30%.

4. The PTC composite material according to any one of claims 1 to 3, characterized in that: After the PTC composite material is compounded with the electrode, the sheet resistance of the PTC composite material formed by drying is 100 to 1000Ω; The temperature control point range of the PTC composite material is 40° C.-52° C., the response time of the PTC composite material to temperature is 5 s, and the temperature control accuracy of the PTC composite material is ±0.4° C.

5. The method for preparing the PTC composite material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: (1) adding ethylene vinyl acetate to an organic solvent, stirring and homogenizing, and obtaining an EVA solution with a mass fraction of 4 to 30%; (2) adding a phase change material to the EVA solution obtained in step (1), stirring and homogenizing to obtain an EVA-phase change material mixed solution, wherein the mass ratio of the added phase change material to the added ethylene-vinyl acetate copolymer is 0.5-1.5:1; the phase change material is hexadecanoic acid and stearic acid; the mass ratio of the added hexadecanoic acid to the stearic acid is 1-4:1-4; (3) Adding a conductive filler to the EVA-phase change material mixed solution obtained in step (2), wherein the mass fraction of the conductive filler in the mixed solution is 4 to 16%, stirring and homogenizing to obtain a PTC composite material; the conductive filler includes but is not limited to graphite powder and graphene.

6. The preparation method according to claim 5, characterized in that: The method of homogenizing after mixing can make the filler distribution more uniform; preferably, the phase change material is hexadecanoic acid and stearic acid; the ratio of hexadecanoic acid and stearic acid added is 1-4:1-4; preferably, the organic solvent includes but is not limited to toluene, tetrahydrofuran, N,N-dimethylformamide; preferably, the ethylene-vinyl acetate copolymer matrix material is EVA with a mass fraction of VA of 10-30%.

7. A method for improving the response speed of a PTC composite material to temperature and / or the PTC strength, characterized in that: The method comprises the following steps: using ethylene-vinyl acetate copolymer as a matrix material, hexadecanoic acid and stearic acid as phase change materials, and graphite powder and / or graphene as a conductive filler to prepare a PTC composite material; Preferably, the method is to use an additive manufacturing process to compound the prepared PTC composite material with an electrode, wherein the additive manufacturing process includes but is not limited to one or more of screen printing, coating, and spin coating, and the sheet resistance of the dried film of the PTC composite material is 100 to 1000Ω; The hexadecanoic acid and stearic acid are added in a ratio of 1-4:1-4.

8. The method according to claim 7, characterized in that The method specifically comprises: (1) adding ethylene vinyl acetate to an organic solvent, stirring and homogenizing, and obtaining an EVA solution with a mass fraction of 4 to 30%; (2) adding the phase change material to the EVA solution obtained in step (1), stirring and homogenizing to obtain an EVA-phase change material mixed solution, wherein the mass ratio of the added phase change material to the added ethylene-vinyl acetate copolymer is 0.5-1.5:1; (3) Adding a conductive filler to the EVA-phase change material mixed solution obtained in step (2), wherein the mass fraction of the conductive filler in the mixed solution is 4 to 16%, stirring and homogenizing to obtain a PTC composite material; the conductive filler includes but is not limited to graphite powder and graphene.

9. The method according to claim 7 or 8, characterized in that: The organic solvent includes but is not limited to toluene, tetrahydrofuran, and N,N-dimethylformamide; preferably, the ethylene-vinyl acetate copolymer matrix material is EVA, and the mass fraction of VA in the EVA is 10-30%.

10. Use of the PTC composite material according to any one of claims 1 to 4, or the preparation method according to claim 5 or 6, or the method according to any one of claims 7 to 9 in the preparation of electrodes, batteries, self-regulating heating components, temperature sensors, detectors, instruments requiring temperature control, and / or wearable electronics.

Citation Information

Patent Citations

  • Shaped phase-change material capable of enhancing heat storage and exchange efficiencies and preparation method thereof

    CN102977860A

  • High-molecular composite material with low curie point and positive temperature coefficient as well as preparation method and application of high-molecular composite material

    CN117551317A

  • A composite phase change material and its method of preparation thereof

    US20230183539A1